2010
DOI: 10.2147/dhps.s7829
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α inhibitors: are they carcinogenic?

Abstract: Biologic therapy has increasingly been used in the treatment of chronic diseases. Tumor necrosis factor (TNF) is a cytokine implicated in the pathogenesis of rheumatoid arthritis and inflammatory bowel disease. Anti-TNF therapy is being used in the treatment of these conditions. Since the introduction of anti-TNF agents, there have been many case reports of development of malignancy after the initiation of anti-TNF therapy. With increasing case reports, there is growing concern that anti-TNF therapy, albeit us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Tumor necrosis factor (TNF) inhibitors are commonly utilized medications for the treatment of immune mediated conditions including ankylosing spondylitis, inflammatory bowel disease (IBD), psoriasis and rheumatoid arthritis (RA) (1, 2). Chimeric, partly humanized, or fully human monoclonal antibodies or antibody fragments have been compared with placebo in randomized controlled trials and have demonstrated efficacy for the management of IBD (3), psoriasis (4) and RA (5).…”
Section: Introductionmentioning
confidence: 99%
“…Tumor necrosis factor (TNF) inhibitors are commonly utilized medications for the treatment of immune mediated conditions including ankylosing spondylitis, inflammatory bowel disease (IBD), psoriasis and rheumatoid arthritis (RA) (1, 2). Chimeric, partly humanized, or fully human monoclonal antibodies or antibody fragments have been compared with placebo in randomized controlled trials and have demonstrated efficacy for the management of IBD (3), psoriasis (4) and RA (5).…”
Section: Introductionmentioning
confidence: 99%
“…TNF-α is a cytokine with pleiotropic activity, and plays a crucial role in inflammation, exhibiting pro-inflammatory characteristics and influencing various aspects of inflammation and immune regulation. Concerns have arisen about the potential induction of immunotolerance by anti-TNF treatment, leading to the development of malignancies [ 128 ]. However, we found a low risk of cancer with these agents, higher in RA patients with other comorbidities such as advanced age, exposure to other immunosuppressants, and/or hematological disorders [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, being a double sword tool, TNF-α may play a defensive role by stimulating NK and cytotoxic T lymphocytes, but can also be “offensive” acting as mediator of cancer development through chronic inflammation promotion [ 13 ]. Thus, in theory, TNF-α antagonists may either promote or inhibit cancer growth [ 32 ]. The onset of B-cell lineage lymphomas and hepatosplenic T cell lymphoma (HSTCL) has been observed in patients with Crohn’s disease who received anti-TNF-α agents mainly in association to thiopurines [ 33 35 ].…”
Section: Discussionmentioning
confidence: 99%